Multimorbidity patterns and its associations with health literacy in chronic kidney disease patients. (20th October 2021) - Gurgel do Amaral, M; Reijneveld, SA; Meems, LMG; Almansa, J; Navis, GJ; de Winter, AF
Abstract: Background: Health literacy is the ability to deal with information related to one's health. Patients with low health literacy have poor disease-management skills for chronic diseases, such as chronic kidney disease (CKD). This could influence the number and combination of their diseases. Methods: We included adult patients with CKD stages 1-5 from the Lifelines Study (n = 2, 742). We assessed the association between low health literacy and the number and patterns of comorbidities, overall and by age and sex, using multinomial logistic regression and latent class analysis, respectively. Results: Low health literacy was associated with a higher number of comorbidities in the crude models, and after adjustment for age, sex, eGFR, smoking, and BMI. In the crude model, the OR for low health literacy increased from 1.71 (1.25 to 2.33) for two comorbidities to 2.71 (2.00 to 3.68) for four comorbidities. In the fully-adjusted model, the associations remained significant with a maximum OR of 1.70 (1.16 to 2.49) for four comorbidities. The patterns of multimorbidity were similar for low and adequate health literacy, overall and by sex, and slightly different for patients older than 65. Older patients with low health literacy had higher comorbidity prevalence and a relatively greater share of cardiovascular, psychiatric, and central nervous system diseases. Conclusions: This study showed that CKD patients have a high prevalence of comorbidities. Patients with low health literacy are more likely to have a higher number of comorbidities than patients with adequate health literacy. Moreover, the multimorbidity patterns are similar for both groups of health literacy, differing slightly at older ages. This age difference suggests that the negative effects of low health literacy develop when aging. Therefore, low health literacy could be an intervention target to decrease multimorbidity along the life course of CKD patients. Key messages: Among CKD patients, low health literacy is associated with more multimorbidity. Health literacy does not affect patterns of multimorbidity in younger patients, but it does slightly in older ones.